2015
DOI: 10.1080/01411594.2015.1020310
|View full text |Cite
|
Sign up to set email alerts
|

Composition-related structural, thermal and mechanical properties of Ba1−xSrxTiO3ceramics (0 ≤x≤ 0.4)

Abstract: The Ba 1¡x Sr x TiO 3 (BST) ceramics were prepared by conventional ceramic method. The crystalline structure and morphology were studied by X-ray diffraction and scanning electron microscopy, respectively. Experimental results show that increase of sintering temperature leads to an uncontrolled precipitating of the phase with a lower content of Ti. The dielectric constant and specific heat as a function of composition and temperature were investigated. The increasing concentration of Sr ions leads to a shift o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The BST particle size increased as the sintering temperature increased due to reduced porosity and changes in densification. This result agrees with the results by Yanling et al 16 Dielectric constant.-The dielectric constant of BST compounds was based on their physical properties and how compounds were manufactured. The dielectric constant increased as the sintering temperature increased due to the improved crystallinity, growth grain size, and degree of crystallization's influence on the dielectric characteristics.…”
Section: Resultssupporting
confidence: 91%
“…The BST particle size increased as the sintering temperature increased due to reduced porosity and changes in densification. This result agrees with the results by Yanling et al 16 Dielectric constant.-The dielectric constant of BST compounds was based on their physical properties and how compounds were manufactured. The dielectric constant increased as the sintering temperature increased due to the improved crystallinity, growth grain size, and degree of crystallization's influence on the dielectric characteristics.…”
Section: Resultssupporting
confidence: 91%
“…It suggested that codoped BST ceramics were relaxor ferroelectric materials with abnormal dielectric characteristics. The Curie temperatures of 1ExY‐BST were about 343 K, 341 K, 340 K and 338 K from 1E3Y‐BST to 1E11Y‐BST, in comparison with about 348 K for Ba 0.8 Sr 0.2 TiO 3 . The crystal below the Curie temperature was with a tetragonal structure while above the Curie temperature was with a cubic structure, which meant there was a ferroelectric‐paraelectric phase transition.…”
Section: Resultsmentioning
confidence: 93%
“…For the sake of reducing the Curie temperature of BaTiO 3 , SrTiO 3 had been combined with BaTiO 3 , forming the solid solution of Ba 1− x Sr x TiO 3 . It was reported to manipulate the Curie temperature values of Ba 1− x Sr x TiO 3 by changing the Sr concentration in the sample, and then resulted in the new and improved ferroelectric properties of the sample . To sum up, doping rare earth ions in BaTiO 3 has turned out to be an effective method for adjusting the dielectric and optical properties.…”
Section: Introductionmentioning
confidence: 99%